The Tailor of Gloucester - Potter, Beatrix (Penguin Group, 1994)
The Tailor of Gloucester was first published in 1903 and tells the story of a poor tailor trying to survive in his freezing workshop over a hard winter. He has a terribly important commission to complete for the Mayor of Gloucester's wedding on Christmas Day but is ill and tired, and before long is running out of food and thread, as well as time! How will he possibly complete the beautiful coat and embroidered waistcoat? Luckily, there lives in the dresser, some very kind and very resourceful mice who set about helping the poor tailor with his work. Not only are they exceedingly helpful, but they are also, luckily, far far too clever for the tailor's sly cat, Simpkin.
Keywords: Animals; General; Juvenile Fiction